Discursive Representation of Teacher Identity in News Media Articles - Bayate, Trecia Lynn; Delos Reyes, Jessa; Payao, Sofel Joy; Gildore, Phyll Jhann (International Journal Corner of Educational Research, 2024)
Teacher identity is discursively represented in the discursive spaces of the news media, which influence the public opinion on teachers and the teaching profession in general. Informed by Systemic Functional Linguistics, specifically Halliday's transitivity analysis, this study analyzed these discursive representations in 30 news media articles from three of the largest news media outlets in the Philippines. It was found that teachers are ascribed to material, mental, verbal, relational, and behavioral processes. As participants in the process types, it was revealed that the teachers were discursively represented as perpetrators, victims, and role models. This reveals the discursive representations of teacher identity in media that are perpetuated in the public discourse consumed by educational stakeholders.